Model Pembelajaran Flipped Classroom Dalam Pembelajaran Ketrampilan Membaca di MTs Al-Hikmah Brebes - Kanza Rufaida; Muassomah Muassomah (Tarling : Journal of Language Education, 2021)
This research aims to determine the application of Flipped Classroom in learning reading skills, and determine its effectiveness in learning reading skills. This research uses descriptive qualitative. This research shows the application of the Flipped Classroom model in learning reading skills with reference to indicators that must be mastered. With this learning model, students are able to understand the reading text correctly, to translate the text, and to retell it in their own language. The researchers concluded that the application of the Flipped Classroom can improve students' reading comprehension.